Efeitos do treinamento com método pilates na força dos músculos do assoalho pélvico de mulheres continentes e incontinentes - Andrade, Carine Laura de (2020)
Aim: To verify the impact of 24-session Pilates program in pelvic floor muscles (PFM) strength in continent and incontinent women. Methods: Clinical trial, with two groups of female: incontinent (IG) and continent (CG). Primary outcome measure was pelvic floor muscle strength measured by digital palpation (Modified Oxford grading system) and manometry by means of Peritron. The frequency of urinary loss was assessed using the voiding diary for 7 days and quality of life was assessed using the international incontinence consultation questionnaire - short form (ICIQ-SF), the pelvic floor impact questionnaire (PFIQ-7) and the pelvic floor distress questionnaire (PFDI-20). The intervention protocol included 24 Pilates solo sessions performed in groups, three times a week for 8 weeks. Voluntary contraction of MAP was not requested during the exercises Results: There was no difference in the strength of the intra-group MAP measured by the Oxford scale or by the manometry for the IG or CG. The comparison between groups for the Oxford scale showed no difference, with an average difference of 0.31 (95% confidence interval [CI]: -0.76 to 0.14) and effect size of 0.42. A similar result was found for the evaluation with manometry with an average difference between the groups of -2.56 (95% CI -7.86 to 2.74) and effect size of 0.16. Regarding the frequency of urinary loss in the GI group, no difference was found before 1.0 (0 - 2.4) and after 0.4 (0 - 2.0) of the intervention (p = 0.162, effect size: 0.11), however, the final score of ICIQ-SF showed improvement before (13.0 [9.0 - 15.0]) and after (9.0 [6.0 - 14.0]) intervention (p = 0.006, effect size: 0.43), the final PFIQ-7 score showed improvement before (42.4 [ 18.9 - 94.8]) and post (23.6 [0 - 56.6]) intervention (p = 0.001, effect size: 0.59), and the final PFDI-20 score showed improvement before (95.7 [42.5 - 135.5]) and after ( 58.2 [28.1 - 116.5]) intervention (p = 0.003, effect size: 0.47). Conclusion: The Pilates program without the request for voluntary contraction of the MAP does not increase the strength of the MAP of continent and incontinent women, does not reduce the frequency urinary loss of incontinent women, however it is able to improve the quality of life perceived by incontinent women.